Food-poisoning from Minas-type cheese, contamined with Staphylococcus aureus - Sabioni, José Geraldo; Hirooka, Elisa Yoko; Souza, Maria de Lourdes R. de (Revista de Saúde Pública, 1988)
An outbreak of food poisoning which occurred in July, 1987, in the city of Ouro Preto, State of Minas Gerais, Brazil, is reported. The food involved was a Minas-type cheese, contamined by Staphylococcus aureus to the level of 9.3 x 10(7) CFU/g. Enterotoxin producing strains of types A,B,D and E were detected. The sample analysed also showed contamination by fecal coliforms above 1.1 x 10(5)/g (MPN), but Salmonella were not present. Due to characteristic symptoms and high contamination it was concluded that Staphylococcus aureus was the pathogene responsible for the outbreak.